PMSM sliding mode control based on novel reaching law and extended state observer. (August 2022) - Li, Shuai; Wang, Hai; Li, Henian; Yang, Chunlai
To improve the dynamic quality and control performance of the permanent magnet synchronous motor speed control system, a novel sliding mode control method with improved reaching law for PMSM was proposed, which has a shorter reaching time and small system chattering. An extended state observer (ESO) based on the hyperbolic tangent function for the sliding mode controller is designed to realize the real-time tracking of the mechanical angular velocity and load disturbance of the motor, which can weaken the influence of the internal parameter perturbation and external load disturbance. The performance of the novel sliding mode controller for PMSM was simulated based on MATLAB/Simulink. An experimental platform based on dSPACE is built. The simulation and experimental results show that this novel PMSM controller can effectively suppress the system chattering and improve the dynamic performance and robustness of the system.